Quality of life and related constructs in a group of infertile Hungarian women: a validation study of the FertiQoL - F. Szigeti, Judit; Grevenstein, Dennis; Wischmann, Tewes; Lakatos, Enikő; Balog, Piroska; Sexty, Réka (Human fertility, 2022)
Quality-of-life measurement is a basic prerequisite for psychologically sensitive fertility care and the FertiQoL is a psychometrically sound outcome measure in this field. The aim of the present research was to investigate the reliability and validity of the Hungarian Core FertiQoL. Two independent samples of infertile women were merged (n = 320). While the model fit of the four-factor Confirmatory Factor Analysis was under the level of acceptability (χ2(246) = 626.36, p < 0.001, RMSEA = 0.070 [CI90 = 0.063-0.076], CFI = 0.878, SRMR = 0.071), the four-factor Exploratory Structural Equation Model showed much improved model fit (χ2(186) = 395.63, p < 0.001, RMSEA = 0.059 [CI90 = 0.051-0.067], CFI = 0.933, SRMR = 0.035). Good internal consistency (Cronbach’s Alphas 0.77-0.92) and construct reliability (0.75-0.95) were found for both factor structures. Depression correlated negatively with fertility-specific quality of life. Almost a quarter of the sample suffered from moderate-to-severe depression. Multivariate analysis of variance indicated that Beck Depression Inventory categories (mild, moderate etc.) co-occurred with significantly distinct FertiQoL score ranges, leading to a possible, clinically meaningful threshold on the Core FertiQoL. Pearson coefficients showed secondary infertility, rural residency and pre-treatment status to be associated with better fertility quality of life.